1996
DOI: 10.1007/s004450050130
|View full text |Cite
|
Sign up to set email alerts
|

Degassing during magma ascent in the Mule Creek vent (USA)

Abstract: The structures and textures of the rhyolite in the Mule Creek vent (New Mexico, USA) indicate mechanisms by which volatiles escape from silicic magma during eruption. The vent outcrop is a 300-m-high canyon wall comprising a section through the top of a feeder conduit, vent and the base of an extrusive lava dome. Field relations show that eruption began with an explosive phase and ended with lava extrusion. Analyses of glass inclusions in quartz phenocrysts from the lava indicate that the magma had a pre-erupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(124 citation statements)
references
References 24 publications
(38 reference statements)
3
120
1
Order By: Relevance
“…We also see evidence for outgassing via shear-induced fracture and healing of the melt, also observed during shearing of analogue silicic magma samples (Okumura et al, 2010;Shields et al, 2014) and in natural samples (e.g., (Stasiuk et al, 1996;Tuffen et al, 2003;Castro et al, 2012;Cabrera et al, n.d.). Fig.…”
Section: Effect Of Shear On Obsidian Degassing and Outgassingsupporting
confidence: 55%
See 2 more Smart Citations
“…We also see evidence for outgassing via shear-induced fracture and healing of the melt, also observed during shearing of analogue silicic magma samples (Okumura et al, 2010;Shields et al, 2014) and in natural samples (e.g., (Stasiuk et al, 1996;Tuffen et al, 2003;Castro et al, 2012;Cabrera et al, n.d.). Fig.…”
Section: Effect Of Shear On Obsidian Degassing and Outgassingsupporting
confidence: 55%
“…Early work by (Eichelberger et al, 1986) suggested that silicic magma rises as a highly permeable foam which, upon extrusion, loses gas via development of bubble connectivity, enabling outgassing to the conduit walls (Jaupart & Allegre, 1991). Another body of work describes shear-induced fracturing of magma, leading to permeable pathways through which volatiles can escape (Stasiuk et al, 1996;Gonnerman & Manga, 2003;Okumura et al, 2009;Cabrera et al, 2010;Castro et al, 2012). There is widespread evidence for this non-explosive magma fragmentation, in the form of brittle fracture and healing.…”
Section: Effusive Silicic Volcanismmentioning
confidence: 99%
See 1 more Smart Citation
“…1). They occur in obsidian domes, vitrophyric ash-flow tuffs (e.g., Smith et al 2001), largevolume rhyolite flows such as those at Yellowstone (e.g., Wright, 1915), and in shallow volcanic conduits (e.g., Stasiuk et al, 1993;Tuffen and Castro, 2009). Spherulites nucleate and grow in response to large undercoolings (>200°C) rapidly imposed on the magma by its degassing and quenching (e.g., Swanson et al, 1989).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…This may be responsible for the peculiar crease structures which characterize such phases of dome growth [Anderson and Fink, 1990]. In a dome, depending on its thickness, [Stasiuk et al, 1996]. $tasiuk et al [1996] proposed that vesicular magma was permeable and able to leak gas to the surrounding country rock, but there are several difficulties with this explanation, as discussed by Jaupart [1998].…”
Section: Variations Of Gas Overpressure During Eruptionmentioning
confidence: 99%